Świadomość ekologiczna studentów - prawda czy fikcja? - Kryk, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Ecological awareness of people is one of the factors conditioning solving environmental problems. There are different kinds of this awareness among others real and ideal. Considering these two types of the ecological awareness a purpose of the article is the attempt of the assessment of the real ecological awareness level of students who because of their education become potential candidates for the social elite having influence on views and the attitude of different social groups. On that account the article: presents research findings of the real ecological awareness of students on the example of students of the Faculty of Economics and Management of the University of Szczecin, compares the level of the ecological awareness of examined students with the level of the ecological awareness of the so-called statistical Pole in order to determine on what level the opinions of students are similar to the opinions of all examined Poles. In comparison are used findings of all-Polish examinations carried out by Public Opinion Research Centre in 2004. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 48-60